Effect of wear conditions, parameters and sliding motions on tribological characteristics of basalt and glass fibre reinforced epoxy composites - Talib, Anis Adilah Abu; Jumahat, Aidah; Jawaid, Mohammad; Sapiai, Napisah; Leao, Alcides Lopes [UNESP] (MDPI, 2021)
Basalt fibre is a promising mineral fibre that has high potential to replace synthetic based glass fibre in today’s stringent environmental concern. In this study, friction and wear characteristics of glass and basalt fibres reinforced epoxy composites were studied and comparatively evaluated at two test stages. The first stage was conducted at fixed load, speed and distance under three different conditions; adhesive, abrasive and erosive wear, wherein each composite specimens slide against steel, silicon carbide, and sand mixtures, respectively. The second stage was conducted involving different types of adhesive sliding motions against steel counterpart; unidirectional and reciprocating motion, with the former varied at pressure—velocity (PV) factor; 0.23 MPa·m/s and 0.93 MPa·m/s, while the latter varied at counterpart’s configuration; ball-on-flat (B-O-F) and cylinder-on-flat (C-O-F). It was found that friction and wear properties of composites are highly dependent on test conditions. Under 10 km test run, Basalt fibre reinforced polymer (BFRP) composite has better wear resistance against erosive sand compared to Glass fibre reinforced polymer (GFRP) composite. In second stage, BFRP composite showed better wear performance than GFRP composite under high PV of unidirectional sliding test and under B-O-F configuration of reciprocating sliding test. BFRP composite also exhibited better friction properties than GFRP composite under C-O-F configuration, although its specific wear rate was lower. In scanning electron microscopy examination, different types of wear mechanisms were revealed in each of the test conducted.
Keywords: Abrasive wear; Adhesive wear; Basalt fibre; Erosive wear; Glass fibre; Polymer composites; Reciprocating adhesive wear